2002
DOI: 10.1002/kin.10098
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic evidence of a common mechanism in the oxidations of diethyl sulfide by dichromates and halochromates of heterocyclic bases

Abstract: The oxidations of diethyl sulfide by potassium dichromate, pyridinium dichromate, quinolinium dichromate, imidazolium dichromate, nicotinium dichromate, isonicotinium dichromate, pyridinium fluorochromate, quinolinium fluorochromate, imidazolium fluorochromate, pyridinium chlorochromate, quinolinium chlorochromate, and pyridinium bromochromate follow identical kinetic orders-first-order each with respect to the chromium(VI) reagents, sulfide and hydrogen ion, and moderately inhibited by manganese(II) ion. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…However, it is observed that in the lower regions of [Cr(VI)], the pseudo-first order rate constant increases with decrease in [Cr(VI)] ( Table 1). Such type of decrease in rate with increase in [Cr(VI)] has been observed by several researchers [33][34][35][36]. However, the rate constants remain constant at higher concentration range of Cr(VI).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…However, it is observed that in the lower regions of [Cr(VI)], the pseudo-first order rate constant increases with decrease in [Cr(VI)] ( Table 1). Such type of decrease in rate with increase in [Cr(VI)] has been observed by several researchers [33][34][35][36]. However, the rate constants remain constant at higher concentration range of Cr(VI).…”
Section: Resultssupporting
confidence: 53%
“…However, the rate constants remain constant at higher concentration range of Cr(VI). The decrease in rate with increase in Cr(VI) in lower concentration region may be due to the dimerization of Cr(VI) followed by decrease in concentration of active species [33][34][35] or due to the existence of some sort of weak association between monomeric Cr(VI) species [36]. The reaction is first order each in PSAA and oxalic acid, which are evidenced from the constant values obtained by dividing k 1 Table T1) and shows a first order dependence with respect to [H + ].…”
Section: Resultsmentioning
confidence: 99%
“…So are those dealing with the structure–reactivity relationships operating in these oxidations 8, 9. But reports on comparison of the rates and mechanisms of oxidations of a substrate by these reagents are a few; diphenyl sulfide in glacial acetic acid 10, diethyl sulfide 11, benzyl alcohol 12, 2‐propanol 13, and 1‐pentanol 14 in aqueous acetic acid individually exhibit identical kinetic behavior on oxidation with dichromates and halochromates of heterocyclic bases. Here, for the first time, we compare the reaction constants of the oxidations by dichromates, fluorochromates, chlorochromates, and bromochromate of heterocyclic bases; primary aliphatic alcohols have been chosen for the study, as the oxidation mechanism has been elucidated recently 14.…”
Section: Introductionmentioning
confidence: 99%
“…So are those dealing with the structure-reactivity relationships operating in these oxidations [8,9]. But reports on comparison of the rates and mechanisms of oxidations of a substrate by these reagents are a few; diphenyl sulfide in glacial acetic acid [10], diethyl sul- fide [11], benzyl alcohol [12], 2-propanol [13], and 1-pentanol [14] in aqueous acetic acid individually exhibit identical kinetic behavior on oxidation with dichromates and halochromates of heterocyclic bases. Here, for the first time, we compare the reaction constants of the oxidations by dichromates, fluorochromates, chlorochromates, and bromochromate of heterocyclic bases; primary aliphatic alcohols have been chosen for the study, as the oxidation mechanism has been elucidated recently [14].…”
Section: Introductionmentioning
confidence: 99%